Helping People Change - Boyatzis, Richard; Smith, Melvin; Van Oosten, Ellen (Ascent Audio, 2019)
You're trying to help-but is it working? Helping others is a good thing. Often, as a leader, manager, doctor, teacher, or coach, it's central to your job. But even the most well-intentioned efforts to help others can be undermined by a simple truth: We almost always focus on trying to "fix" people, correcting problems or filling the gaps between where they are and where we think they should be. Unfortunately, this doesn't work well, if at all, to inspire sustained learning or positive change. There's a better way. In this powerful, practical book, emotional intelligence expert Richard Boyatzis and Weatherhead School of Management colleagues Melvin Smith and Ellen Van Oosten present a clear and hopeful message. The way to help someone learn and change, they say, cannot be focused primarily on fixing problems, but instead must connect to that person's positive vision of themselves or an inspiring dream or goal they've long held. This is what great coaches do-they know that people draw energy from their visions and dreams, and that same energy sustains their efforts to change, even through difficult times. In contrast, problem-centered approaches trigger physiological responses that make a person defensive and less open to new ideas.